2009
DOI: 10.1108/00021460911002680
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting precautionary savings of self‐employed farm households

Abstract: Purpose -The purpose of this paper is to empirically investigate the effects of farm income variability, farm size, and other socio-demographic characteristics on the precautionary saving behavior of farm households and to estimate the influences of the identified factors on the amount of savings by self-employed farm households. Design/methodology/approach -Using 2003 Agricultural Resource Management Survey (ARMS) data and a Double-Hurdle procedure, the likelihood and the amount of savings by farm households … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…They revealed that age has a negative effect on a farmer's adoption of precautionary savings. Mishra [65] conveyed that adoption of precautionary savings had a positive relationship with age. Farmers with more education are more expected to avoid adoption of precautionary savings for managing farming risks.…”
Section: Results Of Individual and Bivariate Probit Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that age has a negative effect on a farmer's adoption of precautionary savings. Mishra [65] conveyed that adoption of precautionary savings had a positive relationship with age. Farmers with more education are more expected to avoid adoption of precautionary savings for managing farming risks.…”
Section: Results Of Individual and Bivariate Probit Modelsmentioning
confidence: 99%
“…The outcome of the education factor is in agreement with Kouame [37] and Raza Ullah et al [23], who established that literacy has a negative relationship with precautionary savings. However, Mishra [65] perceived a positive relationship between the education of the heads of the household and precautionary savings.…”
Section: Results Of Individual and Bivariate Probit Modelsmentioning
confidence: 99%
“…Several studies have investigated the size and the distribution of wealth among farm families (e.g., Wunderlich 1984;Skees, Reed, and Pederson 1985;Ahearn and El-Osta 1991;El-Osta and Morehart 2002;Mishra et al, 2002;Mishra and Chang 2009). Notwithstanding the contribution of these studies, there seems to be a scarcity of literature regarding the impact of the life cycle on the disparity in farm household wealth.…”
Section: Introducationmentioning
confidence: 99%
“…A higher income risk results in an increase in the level of these financial resources. Mishra and Chang (2009) stressed that the stabilisation-oriented policies consequently reduced the income variability, and, as a result, reduced the level of the precautionary savings. Blanck and Bahrs (2009) analysed if the income deposits as an income risk management tool may be doi: 10.17221/123/2016-AGRICECON implemented to the German agriculture sector.…”
Section: Reviewmentioning
confidence: 99%
“…They underlined a significant "off-farm labour state dependence", with interrelations between the past and present farm behaviour. Mishra and Chang (2009) analysed what determined the precautionary savings of the U.S. farm households. A higher income risk results in an increase in the level of these financial resources.…”
Section: Reviewmentioning
confidence: 99%